2017
DOI: 10.1002/iub.1640
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular structures: Quality assessment and biological interpretation

Abstract: Structure determination using X-ray crystallography involves collection of diffraction data, determination of initial phases followed by iterative rounds of model building and crystallographic refinement to improve the phases and minimize the differences between calculated and observed structure factors. At each of these stages, a variety of statistical filters exist to ensure appropriate validation. Biologically important observations often come from interpretations of signals that need to be carefully deciph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…One model [45] was flagged by CheckMyMetal [28] as containing an unusual metal coordination. A study [46] flagged by Salunke and Nair [47] as a case of an electron density map for a ligand contoured at very low level, revealed amongst other errors a different ligand (buffer) in the electron density, which unsupervised methods failed to detect due to an acceptable real space fit and the fact that free amino acid ligands are annotated by the PDB with the same identifier as an amino acid residue and not recognized as a ligand. The example from a recent study [48] was identified based on the correlation emerging between detected errors and certain author clusters.…”
Section: Selection Of Examplesmentioning
confidence: 99%
See 2 more Smart Citations
“…One model [45] was flagged by CheckMyMetal [28] as containing an unusual metal coordination. A study [46] flagged by Salunke and Nair [47] as a case of an electron density map for a ligand contoured at very low level, revealed amongst other errors a different ligand (buffer) in the electron density, which unsupervised methods failed to detect due to an acceptable real space fit and the fact that free amino acid ligands are annotated by the PDB with the same identifier as an amino acid residue and not recognized as a ligand. The example from a recent study [48] was identified based on the correlation emerging between detected errors and certain author clusters.…”
Section: Selection Of Examplesmentioning
confidence: 99%
“…Occasionally, however, the critiqued authors respond by pointing out that similar procedures and results were reported before, sometimes by their critics. For example, Table 1 of [47] lists a dozen structures that were accompanied by publications in which F o - F c omit maps showing putative ligand density were contoured at levels lower than 3σ. We analysed the six structures with maps contoured at 1.5σ and concluded that such low level was completely unnecessary for 3r6r [89] and 1ujj [90], since appropriate contour levels show unambiguously the presence of modelled ligands.…”
Section: Concluding Remarks and Suggestionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is unlike the physiological complexes, which may bind with relatively high affinity with perfect occupancy. It is important to note that if one applies screening criteria based on the high-resolution structures of complexes of high-affinity ligands binding to proteins, such low-affinity leads will certainly be rejected with loss of promising starting compounds [5]. This would be disadvantageous to the very process of drug discovery.…”
Section: Implications Of Multiple Ligand-binding Sitesmentioning
confidence: 99%
“…In any case, the publication of a re‐refined, corrected model is sometimes a complicated ordeal . In addition, it has also been argued by some authors that the different interpretations stem from the inability of the researchers to reproduce the same electron density maps that were used by the original authors …”
Section: Introductionmentioning
confidence: 99%